THE MYTH OF ECONOMIC GROWTH IN TUMPANG PITU GOLD MINE IN BANYUWANGI EAST JAVA - Sandi Pratama Putri, Maghfiroh; Prasetyo Adi, Angga (University of Muhammadiyah Malang, 2020)
Growth becomes a measure in assessing the progress of both countries and regions,to pursue growth will sacrifice the environment on a large scale for the benefit ofcapital that will have an impact on increasing the growth of gross domestic product(GDP). The growth regime will result in environmental exploitation, as happened inthe Banyuwangi Tumpang Pitu gold mine. This study uses the Degrowth approach,which provides a critical view of the forms of growth that are continuously damagingto the environment and choosing alternatives for sustainable growth and can beharmonized with the ecology. Degrowth becomes a foothold in the analysis processto reduce and even eliminate the size of growth that only looks at the aspect ofGDP, which is explained as a regime that massively destroys the environment, ashappened in the Banyuwangi Tumpang Pitu gold mine.